M-Kitchen activities with PPR Lembah Subang (PPR-LS1) community - involvement of some KICT colleagues - Abdul Aziz, Normaziah (Kulliyyah of Information and Communication Technology, IIUM, 2023)
This article shares community activities that mKitchen and Kulliyyah ICT colleagues had organised with B40 community at Lembah Subang ((PPR-LS1).